In memoriam - Čufar, Katarina (Les (Ljubljana), 2026)
We remember Prof. Dr Franc Bizjak (1942–2025), who served at the Department of Wood Science and Technology, Biotechnical Faculty, University of Ljubljana (DWST BF UL), from 1985 to 2002, including two terms as Head of Department. In addition to his teaching and research at DWST, he also lectured at the Department of Forestry and Renewable Forest Resources at the BF UL, fostering close links between forestry and wood science and technology, particularly in the fields of economics and organization. Professor Franc Bizjak's legacy is significant and shows that he was an outstanding colleague, connector, and personality.
Keywords: Bizjak, Franc; economics; ekonomika; lesarstvo; wood science and technology